DEVELOPMENT OF PROJECT-BASED LEARNING DIGITAL WORKSHEETS TO ENHANCE INDONESIAN LANGUAGE LEARNING OUTCOMES IN FIFTH-GRADE ELEMENTARY STUDENTS - Ni Luh Putu Rani Diana Putri; Gusti Ayu Sri Wijastini; Ni Luh Putu Ani Lestiani; Ni Nyoman Kurnia Wati (SOSIOEDUKASI, 2026)
This research aimed to develop and evaluate a Project-Based Learning (PjBL)-based digital Student Worksheet (LKPD) to improve Indonesian language learning outcomes for fifth-grade students in Cluster 4 of Tabanan District. Using a Research and Development approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study employed a quasi-experimental pretest–posttest control group design involving 56 fifth-grade students divided into experimental (PjBL-based digital LKPD) and control (conventional printed LKPD) groups. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and learning achievement tests. Validity testing yielded an overall mean score of 3.48 (>3.00), categorized as "very feasible," with Cronbach's Alpha reliability of 0.87. Practicality assessment showed 87.47% positive responses from teachers and students, indicating high usability and acceptance. Effectiveness testing revealed a statistically significant improvement in the experimental group (t = 7.842, p = 0.000 < 0.05) with a normalized gain (N-gain) of 0.52 (medium–high category), compared to the control group (N-gain = 0.23). These findings demonstrate that the PjBL-based digital LKPD is valid, practical, and effective in enhancing both learning outcomes and student engagement in Indonesian language instruction. The product aligns with the Merdeka Curriculum's emphasis on active, collaborative, and contextual learning experiences for elementary students.This is an open access article under the CC–BY-SA license.